Hepatobiliary ascaridiasis in a young adult woman - Pedro Xavier Marin Castro; José Nuñez Moreno; José Zuñiga Bohórquez (Centro Provincial de Información de Ciencias Médicas, 2020)
The case report of a 27 years patient is presented, with history of conventional cholecystectomy for 10 months due to apparent cholecystitis who went to Luis Vernaza Hospital in Guayaquil, Ecuador, presenting jaundice and abdominal pain. Taking into account the clinical, laboratory and imaging findings a sepsis of abdominal focus, cholangitis and choledocolithiasis was diagnosed.  During the surgical intervention the presence of 2 Ascaris lumbricoides and cholesterol calculi in the bile duct was observed, reason why a bilioenteric bypass was carried out.  After some complications such as breathing failure and hemodynamic upset, the patient was discharged from the institution 25 days after the surgery, with follow up in outpatient clinics during 2 months.